Detection of tick-borne pathogens in questing Ixodes ricinus in the French Pyrenees and first identification of Rickettsia monacensis in France - Akl Toufic; Bourgoin Gilles; Souq Marie-Line; Appolinaire Joël; Poirel Marie-Thérèse; Gibert Philippe; Abi Rizk Georges; Garel Mathieu; Zenner Lionel (Parasite, 2019)
Ticks are important vectors of several human and animal pathogens. In this study, we estimated the prevalence of important tick-borne infections in questing ticks from an area in Southwestern France (Hautes-Pyrénées) inhabited by Pyrenean chamois (Rupicapra pyrenaica pyrenaica) experiencing high tick burden. We examined adult and nymph ticks collected by the flag dragging method from 8 to 15 sites in the Pic de Bazès during the years 2009, 2011, 2013 and 2015. PCR assays were conducted on selected ticks for the detection of Borrelia burgdorferi s.l., Babesia spp., Rickettsia spp., spotted fever group (SFG) Rickettsia and Anaplasma phagocytophilum. Randomly selected positive samples were submitted for sequence analysis. A total of 1971 questing ticks were collected including 95 males, 101 females and 1775 nymphs. All collected ticks were identified as Ixodes ricinus. Among them, 696 ticks were selected for pathogen detection and overall prevalence was 8.4% for B. burgdorferi s.l.; 0.4% for Babesia spp.; 6.1% for A. phagocytophilum; 17.6% for Rickettsia spp.; and 8.1% for SFG Rickettsia. Among the sequenced pathogens, we detected in this population of ticks the presence of Babesia sp. EU1 and Rickettsia helvetica, as well as Rickettsia monacensis for the first time in France. The detection of these pathogens in the Pic de Bazès highlights the potential infection risks for visitors to this area and the Pyrenean chamois population.